2017
DOI: 10.1080/00313831.2016.1258726
|View full text |Cite
|
Sign up to set email alerts
|

Lessons Learned from PISA: A Systematic Review of Peer-Reviewed Articles on the Programme for International Student Assessment

Abstract: International large-scale assessments are on the rise, with the Programme for International Student Assessment (PISA) seen by many as having strategic prominence in education policy debates. The present article reviews PISA-related English-language peer-reviewed articles from the programme's first cycle in 2000 to its most current in 2015. Five literature bases were searched, and results were analysed with SPSS. Results map the frequency of publications according to journal, country, and scientific discipline.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
107
0
24

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 213 publications
(134 citation statements)
references
References 102 publications
3
107
0
24
Order By: Relevance
“…That is, while there were publications documenting the outcomes of these ILSAs, the literature we reviewed did not specifically address how these other major ILSAs had made an impact on national educational policy or reforms efforts. This finding may be associated with the global prominence of PISA and OECD's recommendations to countries aspiring to improve their PISA results, as well as the much publicized "PISA Shock" (e.g., Hopfenbeck et al, 2017;OECD, 2014;Waldow, 2009;Young, 2015) some countries have experienced.…”
Section: Methodsmentioning
confidence: 98%
See 1 more Smart Citation
“…That is, while there were publications documenting the outcomes of these ILSAs, the literature we reviewed did not specifically address how these other major ILSAs had made an impact on national educational policy or reforms efforts. This finding may be associated with the global prominence of PISA and OECD's recommendations to countries aspiring to improve their PISA results, as well as the much publicized "PISA Shock" (e.g., Hopfenbeck et al, 2017;OECD, 2014;Waldow, 2009;Young, 2015) some countries have experienced.…”
Section: Methodsmentioning
confidence: 98%
“…Based on the media attention ILSAs receive, particularly after the release of PISA results and international rankings (Baird et al, 2016;Meyer & Benavot, 2013), it appears as though the increased participation in ILSA-related projects and studies has had a profound effect on education and policy discourses globally (Breakspear, 2012;Hopfenbeck et al, 2017), but not necessarily in the ways that make direct causal policy linkages easy to identify. 12 Our review of the literature indicates that some governments appear to have implemented policy changes as a result of ILSAs scores, while others seem to have used these scores to justify and/or accelerate pre-existing school reforms.…”
Section: Review Of the Literature: Ilsas/glms As Tools Of Legitimationmentioning
confidence: 99%
“…The review concluded that the PISA data‐sets had led to progress in educational research in certain areas, but the authors equally pointed to the need for caution when using this research to inform educational policy. A total of 144 articles was found in the category ‘policy impact’, which focused mainly on the effect of PISA on policy and governments in different countries and economies, with an analysis of the different mechanisms and networks that drove the influence on policy (Hopfenbeck et al, , p.13). Some articles discussed the effect on several countries (Grek, ; Sellar & Lingard, ), whilst others focused on individual country cases such as Germany (Klemm, ; Ertl, ; Di Fuccia, Witteck, Markic & Eilks, ).…”
Section: Previous Research On Pisa and Policymentioning
confidence: 99%
“…The results are presented and discussed in relation to previous research in both countries and indicate questions for future research. In a recent review of 654 peer-reviewed articles on PISA, three broad categories were documented for the use of PISA data in educational research: 1) secondary analysis of PISA data, 2) policy impact, and 3) critique (Hopfenbeck, Lenkeit, El Masri, Cantrell, Ryan & Baird, 2017). The review concluded that the PISA data-sets had led to progress in educational research in certain areas, but the authors equally pointed to the need for caution when using this research to inform educational policy.…”
Section: Html?id5495221)mentioning
confidence: 99%
“…However, Indonesia still far behind Singapore, the first country in the 2015 PISA assessment score in the world. A country can lead the PISA ranking with research progress in the field of education that relies on the frequency of publications according to the journal, country, and scientific discipline [11].…”
Section: Introductionmentioning
confidence: 99%